The last whistle: unveiling the relationship between the career path and retirement age in professional soccer - Rebelo, A.; Teixeira, D. S.; Monteiro, D.; Monteiro, R.; Travassos, B. (Journal of Human Kinetics, 2025)
This study explores the relationship between Career Indicators (CIs) and the retiring age of Portuguese soccer players, focusing on the impact of early career experiences and career discontinuation stages. Data were analyzed from retired Portuguese soccer players registered on a private digital platform, using specific CIs related to different stages of their athletic careers. The analysis involved a two-level mediation model incorporating various CIs. Significant direct effects emerged with `the number of seasons as a youth player` and `the number of seasons as a youth player in top 3 clubs` on `retiring age`. Additionally, a strong association was identified between `discontinuation stage length` and `retiring age`. The findings emphasize the importance of effectively managing career discontinuation stages and proactive career planning. Consequently, comprehensive support programs offering resources and guidance for career transitions are recommended for soccer players. The study underlines the key role of stakeholders in enabling smoother transitions into retirement.